Answer: ![\frac{x-4}{2x-2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx-4%7D%7B2x-2%7D)
Step-by-step explanation:
divided by
is the same thing as multiplying
by
.
The equation we get is:
![\frac{2x^2+5x+3}{x^2-3x-4}*\frac{x^2-8x+16}{4x^2+2x-6}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E2%2B5x%2B3%7D%7Bx%5E2-3x-4%7D%2A%5Cfrac%7Bx%5E2-8x%2B16%7D%7B4x%5E2%2B2x-6%7D)
With this equation, we can factor each equation:
![\frac{(x+1)(2x+3)}{(x+1)(x-4)} *\frac{(x-4)(x-4)}{2(x-1)(2x+3)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%2B1%29%282x%2B3%29%7D%7B%28x%2B1%29%28x-4%29%7D%20%2A%5Cfrac%7B%28x-4%29%28x-4%29%7D%7B2%28x-1%29%282x%2B3%29%7D)
We can cancel out like terms since they would be dividing each other:
![\frac{x-4}{2x-2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx-4%7D%7B2x-2%7D)
Answer:
315
Step-by-step explanation:
Area = Length x Width
Area = 21 x 15
Area = 315
Answer: It traveled 36,000 miles per hour.
Step-by-step explanation: 1/10 of a second x 36000 = 1 hour.
Answer:
6(8 -5)
Step-by-step explanation:
take out the 6 -
8 - 5
then put them in parentheses
(8 - 5)
add back the 6
6(8 - 5)
Answer:
X= -13/5
Step-by-step explanation:
i hope this helps :)